Olive floral development in different hedgerow positions and orientations as affected by irradiance - Trentacoste, Eduardo Rafael; Moreno Alías, I.; Gómez del Campo, María; Beyá-Marshall, Victor; Rapoport, Hava F. (2018)
Irradiance received within the olive hedgerow canopy varies with respect to row orientation, spacing and hedge dimensions. These orchard management criteria offer the opportunity for improving productivity based on understanding the responses of yield-determining processes to irradiance. How irradiance influences inflorescence and flower development, the initial steps in fruit formation, are fundamental components of these processes. In this study we evaluated flowering and fruiting parameters in 5 hedgerow positions (defined by hedgerow side and vertical layer above soil) for N–S (North-South) and E–W (East–West) olive hedgerows (cv. Arbequina). The canopy layers and orientations provided a wide gradient of irradiance received and the relationship of estimated mean daily irradiance for annual and for short periods during floral development and initial fruit set was explored. The numbers of inflorescences and fruits per layer increased from the less illuminated base to more illuminated upper canopy layers. Axillary bud number per shoot also increased toward more illuminated positions, while the proportion of floral buds was unresponsive to the irradiance microenvironment at different positions within the hedgerows. Inflorescence length, node and flower number per inflorescence, and perfect flower percentage increased with position illumination. Ovary quality, indicated by ovule differentiation, was consistently high, independent of position, but ovary size showed some slight significant increases with illumination, mainly in the endocarp. Flowers/inflorescence, fruits/fruiting inflorescence and inflorescence and fruit number per position correlated positively and significantly with estimated irradiance similarly for annual and short periods (r range from 0.49 to 0.86). Despite improved flowering parameters with greater irradiance, no consistent differences among positions were found for percentage of inflorescences bearing fruit and fruit number per inflorescence. Instead, our results indicated that different fruit numbers among canopy positions were primarily due to an irradiance effect on vegetative growth, causing more and longer fruiting shoots and therefore more total flowering sites (nodes) per layer, with only a small contribution by inflorescence structure and flower quality.